Reliability of Dot Peen Marking in Product Traceability - Dragičević, Dragan; Tegeltija, Srdjan; Ostojić, Gordana; Stankovski, Stevan; Lazarević, Milovan (International Journal of Industrial Engineering and Management, 2017)
Implementation of product traceability is in interest of every producer because it cuts production cost and provides better security booth for buyers and suppliers. To provide traceability of product parts it is needed to mark each part separately. Dot peen marking is technology where data is printed on product surface by stamping with carbide needle. Research presented in this paper is focused on readability of DataMatrix 2D code made with dot peen marking method. It includes few types of materials and also different parameters of marking (code size and stamping depth). Article history: Received (23.12.2016); Revised (17.01.2017); Accepted (03.04.2017)